2014
DOI: 10.1186/1472-6920-14-12
|View full text |Cite
|
Sign up to set email alerts
|

Why medical students choose psychiatry - a 20 country cross-sectional survey

Abstract: BackgroundRecruitment to psychiatry is insufficient to meet projected mental health service needs world-wide. We report on the career plans of final year medical students from 20 countries, investigating factors identified from the literature which influence psychiatric career choice.MethodsCross sectional electronic or paper survey. Subjects were final year medical students at 46 medical schools in participating countries. We assessed students’ career intentions, motivations, medical school teaching and expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
86
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(102 citation statements)
references
References 63 publications
10
86
0
6
Order By: Relevance
“…A -all trainees in the country, B -statistically rigorous randomised sample of all trainees in the country that controls for possible sources of bias, C -randomised sample consisting of a significant proportion of all trainees in the country but without clear controls for possible sources of bias, D -all trainees from more than one training institution in the country, E -trainees from more than one training institution in the country, F -all trainees from the largest training institution in the country. 2 Number of participants who fully completed the MBI-GS and were included in the final analysis presented in this paper. 3 Percentage of trainees who fully completed the MBI-GS out of all approached trainees in each country.…”
Section: Fundingmentioning
confidence: 99%
See 1 more Smart Citation
“…A -all trainees in the country, B -statistically rigorous randomised sample of all trainees in the country that controls for possible sources of bias, C -randomised sample consisting of a significant proportion of all trainees in the country but without clear controls for possible sources of bias, D -all trainees from more than one training institution in the country, E -trainees from more than one training institution in the country, F -all trainees from the largest training institution in the country. 2 Number of participants who fully completed the MBI-GS and were included in the final analysis presented in this paper. 3 Percentage of trainees who fully completed the MBI-GS out of all approached trainees in each country.…”
Section: Fundingmentioning
confidence: 99%
“…1 Severe burnout was a dichotomous outcome, defined as mean sum scores ≥ 2.20 on the emotional exhaustion (MBI-EX) and ≥ 2.00 on the cynicism (MBI-CY). 2 Total weekly working hours are sum of time spent doing work assignments at one's workplace (mean 48.1, SD 14.3) and at home (mean 5.9, SD 7.1). Two participants did not provide data on their weekly working hours.…”
Section: Fundingmentioning
confidence: 99%
“…The main factors studied include style and quality of life, financial rewards, social prestige, as well as personality characteristics and psychological profiles 1 . Besides these factors, the choice of psychiatry as a specialty is motivated by aspects that include: quality of education in the area during medical graduation, interest even before entering graduation, intellectual challenge, importance of doctor-patient relationship, integration opportunity with other areas, and experience from personal or family experiences of psychological and/or psychiatric problems [2][3][4] .…”
Section: Dear Editormentioning
confidence: 99%
“…Table 1 shows that there is a greater chance of choosing Psychiatry among students who have or had psychiatric symptoms/ disorder and/or are doing or have done psychiatric treatment. Specific studies to evaluate the medical specialty choice had already shown the association between the choice of psychiatry and the experience of personal, familiar or close people psychological/ psychiatric problems 2,3 . Our study pointed to the same direction.…”
Section: Dear Editormentioning
confidence: 99%
“…Algunos de los factores que se han visto asociados con esta preferencia incluyen: gé-nero femenino, experiencia personal y/o familiar de enfermedad mental e interés en la psiquiatría previo a estudiar medicina y que se mantiene durante la carrera. 14 En nuestro país, las plazas ofertadas para realizar la especialidad en psiquiatría no se han incrementado desde el 2007, año en el que se ofertaron 150 plazas. 15 Para el año 2015 se ofertaron 144 plazas, seis lugares menos que los disponibles ocho años atrás.…”
unclassified